As repercussões maternas diante a hospitalização em uma enfermaria pediátrica - MARQUES, Bruna Damasceno (2019)
Hospitalization is a stress and anxiety process, especially when patient is a child, leaving her fragile and afraid of the hospital environment, once that painful procedures usually occur. However, this process does not only in the psychosocial health of the child, as well as those around her. It is fundamental that professionals, especially nurses who are in direct and continuous contact, can take a different look at this mother by providing humanized assistance, allowing a holistic approach, not only focused on the reestablishment of the hospitalized child's health, but to pay attention to the psychosocial health of the companion, who are most often the mother of these children. The objective of this work is to understand and identify maternal repercussions during the period of child hospitalization in the pediatrics sector. It is a field research, an exploratory descriptive study, with a qualitative approach, having as a place of study the Maternal and Child Reference Hospital “Fundação Santa Casa de Misericórdia do Pará”. The interviews were carried out after approval of the Research Ethics Committee, in November, 2018. Fifteen mothers who had children hospitalized in pediatric wards, who met the inclusion criterion, and accepted to participate in the study. The results were obtained through a semi-structured interview script, and were organized and analyzed in three stages, through the analysis of Bardin's discourse, from which the following categories emerged: Feelings experienced during hospitalization; Changes in maternal daily life from hospitalization; Support networks in the context of hospitalization; Difficulties experienced during hospitalization; Practical assistance to the companion. With this study, it was possible to perceive that the mother as a partner is significantly impacted, reflecting on her state of life / health, and the importance of the support networks was perceived, and the presence of the family was recurrent to minimize those factors that cause negative impacts. Research also evidenced the lack of an individualized look at the different singularities existing in the hospital environment, and the lack of integral assistance, since many testimonies about multiprofessional assistance, and the professional nurse itself, revealed that mothers were not included in care, and that health care was directed only at the child. This In order to ensure quality care, it is necessary to understand that during the hospitalization period, the mother and child are a single set, and that the companion needs to be inserted into the interventions of the hospital staff as a whole, and especially nursing, by having more frequent contact and close to the binomial.